Dinâmica de plantas invasoras em cultivos de mandioca, em ecossistemas amazônicos no Alto Solimões - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Cassava is among the most cultivated and consumed species by the population from its derivatives, such as flour, tucupi and gum, in addition to being a source of income. In the Alto Solimões mesoregion, family farmers plant in terra firme and floodplain ecosystems, where the occurrence of invasive plants is common. These are frequent during the cassava development cycle, which justifies the importance of knowing them. In this sense, the objective of the research was to evaluate the dynamics of invasive plants in cassava plantations in Amazonian ecosystems in Alto Solimões. The research was carried out in 2021 in the communities Guanabara I, in terra firme and São José, in the floodplain. The chemical and physical characteristics of the soils cultivated with cassava, the phytosociological survey of weeds and the morphological description of cassava varieties were analyzed. Information and observations on management practices in the communities were obtained from farmers in the cultivation areas. The lowland soil presented a higher level of fertility in relation to the terra firme soil. According to the botanical classification, 9,369 individuals were found in terra firme, distributed in 34 families and 39 species, while in the floodplain there were 6,112 individuals, 15 families and 25 species. The Monocot class predominated in relation to the Eudicot in both ecosystems. The species Panicum trichoides was the most important and presented the highest dry matter weight. The cassava varieties grown on dry land were Racha terra, Milagrosa, Bacu, Sumaúma, Pão, Tucura and Pirapitinga, and in the floodplain they were Olho Purple and Pirapitinga. Soil, invasive plants and cassava management practices are different due to the characteristics of each ecosystem.
Keywords: Terra firme; Várzea; Ecossistemas amazônicos; Práticas de manejo; Plantios de mandioca; CIÊNCIAS AGRÁRIAS; Infestação; Mandioca; Manihot esculenta